BREACH-METHOD: a new framework to generate event sets for financial flood risk assessment of the Dutch Delta - Kolen, Bas; Nicolai, Robin (Journal of Coastal and Riverine Flood Risk, 2025)
Flood risk is defined as the probability of occurrence multiplied by the consequences, resulting in an annual risk metric. In The Netherlands, flood risk assessments for levees typically assume: 1) all levee sections and flood consequences are independent with no breaches occurring elsewhere in the system, 2) emergency measures are not taken into account, and 3) the definition of failure does not encompass the complete failure process. This method leads to an overestimation of risk and a probability of flooding in the Netherlands exceeding 1/5 per year, despite the last levee failure occurring in 1953, followed by numerous levee reinforcements. While flood protection remains the most cost-effective measure for The Netherlands, a conservative approach can be realistic, especially in light of climate change. However, for risk assessments designed to inform choices on spatial adaptation, mortgages, insurance solutions and stress tests a more realistic approach is needed. In response, our paper proposes an alternative flood risk assessment framework and flood event model. We combine statistical methods and expert judgment tailored to polder systems characterized by complex hydraulic interdependencies. By delineating independent areas and estimating conditional probabilities of single and multiple breach events under varying hydraulic loads—such as river discharge and storm surge—the proposed model delivers a more realistic depiction of failure probabilities in The Netherlands. Consequently, it offers a less conservative local flood risk profile, facilitating informed decision-making across domains such as land use planning, risk insurance, and investment allocation..